Wage-Profit Rate Schedules in Case of Saudi Arabia - Algarini, Abdullah (International Journal of Economics and Financial Issues, 2018)
This paper uses the real wage-profit rate schedule to examine the direction of technical change in Saudi economy during 1990-2016. We find that technical change is Hicks-neutral (i.e., increasing both labor and capital productivity) between 1990 and 2004; and Marx-biased (i.e., increasing labor productivity with declining capital productivity) over the period 2005-2014.The most noteworthy aspect of the Saudi economy pattern of technical change is that it has started to enter a phase of steady decrease in the profit rate and increase in the real wage, as seems to be the historical experience of many developed countries. The growth of real wage continues to grow by increasing 9.6%, 19.5%, and by 130%, while the profit rate grows by 11.8%, 5.7%, and -20.5% in the first three periods, respectively. Keywords: Productivity of labor and capital, Saudi Arabia, capital-labor ratio, wage-profit rate JEL Classifications: E24, J3 https://doi.org/10.32479/ijefi.7250